2020
DOI: 10.14444/7092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cervical Hybrid Reconstructions: A Prospective Study

Abstract: Background: The study design was a prospective clinical cohort study. The aim of this study was to assess the patient-reported outcome measures (PROMs), patient satisfaction, as well as complication and reoperation rate of cervical hybrid procedures for symptomatic cervical multilevel degenerative disc disease (MLDDD). Cervical total disc replacement (CTDR) has been shown to be safe and effective for the treatment of degenerative pathologies. However, there is minimal PROMs data on the outcomes of combined CTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In the current study, improved clinical outcomes reflected by VAS, JOA score, and NDI demonstrated that HS effectively ameliorated neurological symptoms, consistent with previous findings reported by Scott-Young et al. ( 27 ). More importantly, numerous studies in the past linked muscle FI to postoperative pain or neurological deficits, particularly following lumbar spine and posterior cervical surgery ( 4 , 13 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, improved clinical outcomes reflected by VAS, JOA score, and NDI demonstrated that HS effectively ameliorated neurological symptoms, consistent with previous findings reported by Scott-Young et al. ( 27 ). More importantly, numerous studies in the past linked muscle FI to postoperative pain or neurological deficits, particularly following lumbar spine and posterior cervical surgery ( 4 , 13 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a segment with soft protrusions may be treated with CDA, while a segment with osteophytes and severe degeneration may require ACDF. In recent years, various clinical studies have shown that HS can yield satisfactory outcomes while preserving some level of mobility in the cervical spine for continuous two‐ or multi‐level CDDD 15,36,37 . Due to the skipped lesion, HS is considered to be a suitable option for noncontiguous CDDD, as there is a lower likelihood of the CDA level and ACDF level affecting each other.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, various clinical studies have shown that HS can yield satisfactory outcomes while preserving some level of mobility in the cervical spine for continuous two-or multi-level CDDD. 15,36,37 Due to the skipped lesion, HS is considered to be a suitable option for noncontiguous CDDD, as there is a lower likelihood of the CDA level and ACDF level affecting each other. Biomechanical studies have confirmed that the increase in ROM at adjacent segments after HS is lower than that observed with 2-level ACDF, indicating that HS has a less detrimental biomechanical effect on adjacent segments.…”
Section: Cda Presents Biomechanical Advantagesmentioning
confidence: 99%
“…Common contraindications are similar to those described for CDA and include advanced osteoporosis, facet arthropathy, or DDD. 33,34 Given the novel nature of HS, studies assessing long-term reoperation in HS are limited. Zigler et al found that in 115 hybrid surgeries followed for a mean of 6.5 years, only 6 required reoperation with 5 due to adjacent segment disease, and 1 due to pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%